2022
DOI: 10.7759/cureus.20889
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy and Adequacy of Computed Tomography Versus Fluoroscopy-Guided Percutaneous Transpedicular Biopsy of Spinal Lesions

Abstract: BackgroundTranspedicular biopsy of spinal lesions is imperative for the generation of a definite diagnosis. Thus far, literature comparing the accuracy and adequacy between fluoroscopy-guided and computed tomography (CT)-guided transpedicular biopsy of spinal lesions is scarce. We aim to compare the accuracy and adequacy of samples collected with the two techniques at the largest tertiary hospital in Malaysia. Materials and methodsA total of 60 patients (37 patients with spinal infection and 23 patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The diagnostic rate of image-guided percutaneous spinal needle biopsy was reported to be 80–97.3% [ 7 , 8 , 9 , 10 , 11 , 12 ], which is consistent with the present results. Yang et al [ 8 ] reported a decreased diagnostic rate for lesions <20 mm.…”
Section: Discussionsupporting
confidence: 93%
“…The diagnostic rate of image-guided percutaneous spinal needle biopsy was reported to be 80–97.3% [ 7 , 8 , 9 , 10 , 11 , 12 ], which is consistent with the present results. Yang et al [ 8 ] reported a decreased diagnostic rate for lesions <20 mm.…”
Section: Discussionsupporting
confidence: 93%
“…At the time of diagnosis, the average erythrocyte sedimentation rate (ESR) is approximately 60 mm/h [ 18 , 25 , 26 , 53 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Among patients who underwent an uncomplicated discectomy, 97% exhibited c-reactive protein (CRP) values below 2.5 μg/mL, ESR values below 45 mm/h, temperatures equal to or below 37.5 °C, and normal magnetic resonance imaging (MRI) findings within the initial 10 days post-surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Samples (disc material, subchondral bone and abscess fluid) are collected from the affected disc space as well as the surrounding inflammatory soft tissue. Fluoroscopic guide percutaneous transpedicular biopsy offers similar accuracy and adequacy and can be used in cases that CT-guided biopsy is not available [ 59 ]. In a recent systematic review aiming to determine the diagnostic culture yield of CT-guided biopsies performed in cases of suspected spinal infections, the authors reported only 33% diagnostic accuracy of CT-guided biopsies, in terms of positive cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the subsequent treatment of anti-TB medication was deemed ineffective. However, it is worth noting that the puncture biopsy under the guidance of CT is recognized as a critical method of diagnosis in cases of unknown etiology of vertebral body destruction [ 65 ]. Therefore, PMseq of specimens of the L4 vertebral lesion was performed concurrently to detect all possible pathogens.…”
Section: Discussionmentioning
confidence: 99%